A framework for community based management of indigenous cattle genetic resources in Dano district, central Ethiopia - Tesfahun, G.; Ayalew, W.; Abdulai, A.; Wollny, C.B.A.; Bayer, W. (2008)
Despite the significant contribution of cattle to the country, little attention has been given to identify, characterize and conserve the diversity of cattle breeds. This paper presents a unique cattle population found in a monastery in the northwest of Ethiopia referred to as Mahibere–Silassie composite breed. With the view to investigate to what extent the breed in question is different from the rest of the cattle population of the study area a survey work that included focus group discussions, administration of semi-structured and measurement of variations using quantitative and qualitative traits was conducted in 2003. Findings of the study showed that the breed is reported as closed and geographically isolated within the territories of the Mahibere-Silassie Monastery. Also some descriptive data on general husbandry practices, population size, and phenotypic features categorized as primary and secondary features were documented and which further confirmed that the Mahibere-Slassie herd is distinct. Series of different but interlinked statistical tests have confirmed that the breed is basically different from the rest of cattle population of the study area. Particularly, the generated Mahalanobis’ distance matrix of the canonical discriminate analysis from twelve quantitative variables which was used to construct the phenograms or classification trees for the female and male populations, singled out the monastery cattle population far from the rest of the group. Apart from its distinct breed characteristics, the fact that the population has been maintained within the territories of the Monastery in isolation for over three centuries may have particular relevance in the study of evolutionary relationships of cattle breed types in this part of eastern Africa. Therefore, without doubt, the Mahibere-Silasie herd is a unique cattle breed type. However, the effective population size (Ne) of the herd was calculated to be around 94; this low value can cause inbreeding at a rate of about 0.5% per generation. Thus, this herd is vulnerable to sudden or persisting threats that cause loss of genetic diversity and lead to gradual extinction unless urgent genetic conservation measures are taken.